2014
DOI: 10.4049/jimmunol.1302308
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ or IFN-α Ameliorates Chronic Proliferative Dermatitis by Inducing Expression of Linear Ubiquitin Chain Assembly Complex

Abstract: The linear ubiquitin chain assembly complex (LUBAC) ubiquitin ligase complex, composed of HOIL-1L–interacting protein (HOIP), heme-oxidized IRP2 ubiquitin ligase-1L (HOIL-1L), and SHANK-associated RH domain protein, specifically generates linear polyubiquitin chains and is involved in NF-κB activation. Lack of SHANK-associated RH domain protein, which drastically reduces the amount of HOIP and HOIL-1L, causes chronic proliferative dermatitis (cpdm) in mice. Impaired NF-κB activation and augmented apoptosis hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 54 publications
1
10
2
Order By: Relevance
“…A recent report showed that the Rnf31 gene, which encodes HOIP, is located between the Psme2 and Irf9 genes, both of which are induced by interferon‐γ (IFN‐γ). In addition, the Rnf31 gene was shown to have an IFN regulatory factor 1 and two IFN‐γ‐responsive regulatory elements on the upstream and downstream regions of the genes respectively . As expected, mRNA transcription of HOIP was increased after IFN‐γ treatment.…”
Section: Analysis Of the Pathophysiological Roles Of Linear Ubiquitinsupporting
confidence: 63%
See 1 more Smart Citation
“…A recent report showed that the Rnf31 gene, which encodes HOIP, is located between the Psme2 and Irf9 genes, both of which are induced by interferon‐γ (IFN‐γ). In addition, the Rnf31 gene was shown to have an IFN regulatory factor 1 and two IFN‐γ‐responsive regulatory elements on the upstream and downstream regions of the genes respectively . As expected, mRNA transcription of HOIP was increased after IFN‐γ treatment.…”
Section: Analysis Of the Pathophysiological Roles Of Linear Ubiquitinsupporting
confidence: 63%
“…As expected, mRNA transcription of HOIP was increased after IFN-c treatment. Increased protein levels of both HOIL-1L and SHARPIN in addition to HOIP were observed in MEFs, BMDMs, and primary keratinocytes in response to type I and type II IFN, which are induced mainly by immune cells including activated lymphocytes after RNA or DNA virus infection leading to enhanced activation of NF-jB (136). Moreover, intradermal injection of type I or type II IFN ameliorated cpdm dermatitis by upregulating HOIP expression in the skin, indicating that reduction of residual LUBAC underlies cpdm pathology.…”
Section: Analysis Of the Pathophysiological Roles Of Linear Ubiquitinmentioning
confidence: 99%
“…Immunohistochemical analyses of the skin confirmed increased TNF-␣ production presumably from a number of infiltrated inflammatory cells in 5-week-old HOIL-1L ϩ/Ϫ SHARPIN cpdm/cpdm and 12-week-old SHARPIN cpdm/cpdm mice ( Fig. 3E) (31). Phosphorylation of the p65 subunit of NF-B is known to be a reliable marker of NF-B activation (32).…”
Section: Hoilmentioning
confidence: 77%
“…We previously observed that an interferon-mediated increase in LUBAC composed of HOIL-1L and HOIP ameliorates, but cannot completely cure, cpdm symptoms (31). Given that HOIP levels were lower in interferon-treated cpdm keratinocytes than in WT keratinocytes, augmented activation of antiapoptotic NF-B mediated by an increase in HOIL-1L/HOIP-containing LUBAC might not be able to completely override the augmented cell death caused by loss of SHARPIN.…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to identify the cytokine(s) necessary for the observed autocrine/paracrine regulation of HOIL-1L. It has been reported that IFN-α and IFN-γ can regulate the expression of LUBAC components in SHARPIN-deficient mice (43). In our mod-HOIL-1L has several LUBAC-independent functions, such as acting as an E3 ubiquitin ligase to target proteins such as PKCζ for degradation as seen in adaptation to hypoxia and cancer (23,31,39).…”
Section: Iav Infection Increases Hoil-1l Inmentioning
confidence: 99%